El Excentrico, 1968-02-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
February 05, 1968 [5 de enero de 1968]. No volume or issue number. Cover has headshots of five models. Pictured from top left to bottom right are, Cristina Cadena, Rosalinda Santa Cruz, Linda Gonzales, Sussie Lastra, and Marian Zamora. The headline reads, "American GI fourm, S.J. Chapter, 7th Annual Cornation Ball, Saturday, Febrauary 24, 1968, Starlight Ballroom. $6.00 per person."